ROLE OF PATHYA - APATHYA IN MANAGEMENT OF GALAGANDA (HYPOTHYROIDISM) – AN AYURVEDIC PERSPECTIVE (International Journal of Ayurveda and Pharma Research, 2020)
Galaganda is a swelling which hangs over the region of Gala like Mushka either big or small in size and resembles the shape of a scrotal sac. It has been described as a disease entity of impaired Vata, Kapha dosha and Medo dhatu along with involvement of Ama and Dhatvagnimandhya. The concept of Kaphavritavata has also been discussed by some Acharyas with Laskhanas such as Saitya, Gurutva, Sopha which can be compared to symptoms like weight gain, edema etc in hypothyroidism with a specific feature of raised TSH levels, it is correlated to Galaganda in Ayurveda. Modernization leads to improper balance and disintegration of health and environment, body, mind and soul leading to lifestyle disorders. Hypothyroidism is one such lifestyle and metabolic disorder which is commonly encountered now days continuing to pose a major health issue. As it also responds to stress and stimuli the global incidence of hypothyroidism is more. The commonest cause of hypothyroidism is dietary deficiency of Iodine. Pathya and Apathya include materialistic substances and specific regimes which effect the body and mind. This article endeavors to put forward the management of hypothyroidism according to its Nidana in Ayurvedic perspective which would help in understanding the etiopathogenesis of the disease and appropriate management of the disease by following Pathya and avoiding Apathya.